Pertumbuhan dan produksi tanaman stevia (Stevia rebaudiana b.) pada persentase naungan dan umur panen berbeda di dataran rendah - Furri Kurnia Husna; Susilo Budiyanto; Sutarno Sutarno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The purpose of the research was to study the effect of shade percentage and different harvest timeon stevia growth and production in lowland. The experiment was assigned in completely randomized multilocation design with the first factor was shade percentage (45%, 55% and 65%) and the second factor was different harvest time (30 DAP, 40 DAP and 50 DAP). Each treatments was repeated three times. Parameters measured were the plant height, dry weight, total chlorophyll content and total sugar content. Data were subjected to ANOVA and followed by Tukey Test. The result showed that the best shade percentage was 45% in total sugar content. The best harvest time was 50 DAP that showed on total chlorophyll content. The result showed no significant different on average plant height and dry weight. Interaction of shade percentage and different harvest time showed significant effect on total sugar content. Keyword : Stevia, shade percentage, harvest age